Traditional house architecture of the Mandar tribe in West Sulawesi, Indonesia - Rahmansah; Rauf, Bakhrani; Lullulangi, Mithen (2024)
West Sulawesi Province is a Mandar region that is characterized by its traditional house called Boyang Mandar. The purpose of this research is to reveal local wisdom about the concept and construction system of Mandar houses based on the anatomy of the human body. This research method uses a qualitative method with a Case Study Approach. The analysis method used is Discovering Cultural Themes. The results showed that Mandar people use human manifestations, especially homeowners (husband and wife) as the concept and system of the house, both vertically and horizontally, which means that the life of the homeowner will be in harmony with nature in order to be safe and lucky in the house.